Pemberian Makanan Tambahan Kepada Anak-anak Penyitas Banjir di Pidie Jaya Aceh - Wintah Wintah; Kiswanto Kiswanto; Firman Fidauz (Universitas Teuku Umar, 2026)
Flood disasters in Pidie Jaya Regency adversely affect food security and the nutritional status of toddlers due to disrupted access to essential nutrients. This community service aimed to provide local food-based Supplementary Feeding (PMT) in the form of mung bean porridge and soy milk to toddlers in Blang Cut Village. The methods included field observations, nutritional education using visual media, and PMT distribution. The results showed an increase in mothers' nutritional literacy regarding processing affordable local food rich in protein, iron, and zinc. The PMT products had high acceptability as children liked the taste and texture. In conclusion, pulse-based PMT intervention is an effective solution for emergency nutritional fulfillment for flood survivors to prevent stunting risks. Program sustainability is supported by the community's enthusiasm for replicating food processing independently to strengthen post-disaster health resilience.